Curriculum development in American Studies: Interdisciplinarity, student progression, and the Swedish-American paradox - Hjorthén, Adam (Högre utbildning, 2021)
The article explores challenges and possibilities of curriculum development in American Studies in Sweden, a discipline that does not yet exist as a national degree-awarding subject. The aim is to investigate how advanced level learning in American Studies can be designed in relation to student progression. The backdrop to this problem is “the Swedish-American paradox”—the fact the many Swedish students have substantial prior experiences and knowledges about the United States, yet where the opportunities for academic education about North America are rather limited. While American Studies is a common discipline at North American and European universities, it does not have a strong foothold in Sweden. The article discusses the disciplinary history and educational tradition within American Studies, focusing on its interdisciplinarity. It then discusses how interdisciplinarity have been brought into American Studies curricula internationally, and how this sits within the framework of the Swedish Higher Education Ordinance. The American Studies case is juxtaposed to similar fields through a review of area studies MA programs in Sweden. The article ends with an exploration of the ways in which interdisciplinarity can be adopted as a learning outcome in relation to the challenge of student progression in Sweden.